Water as a stimulant for infants' motor development - Numminen, P.; Saakslahti, A. (Biomechanics and Medicine in Swimming VIII, 1999)
Debate on whether the link between specific reflexes and later voluntary movements that they resemble is a direct or an indirect relationship, still prevails unanswered. Among infants some of these reflexes might be stimulated in water. Thus this study tries to ascertain: 1) What are the effects of frequently organised infant swimming on their motor development, and 2) Are there any relationships between the observed differences and various background variables? The subjects (N=32; 21 boys and 11 girls) were randomly divided into Control (CR), Experimental 1 (EXP 1) and Experimental 2 (EXP 2) groups. EXP l participated in 10-25- and EXP 2 in 29-56- sessions of an organised infant swimming program during a nine-month-period. When comparing the means of motor development scores between the groups, EXP 1 group seemed to be ahead of the other groups in I 0 of 22 criteria. Infants' early involvement age correlated significantly with reaching, arm-support, sitting and extension of arms. Of the background variables, parent's age at starting to walk was related to infant's reaching and crawling. There might be a "critical period" for infants to begin infant swimming in order to increase developmental outcomes out of water. The participation frequency of approximately once a week seemed appropriate.